Hepato biliary pancreatic ascariasis: a rare case report - A., Siva Subramanian K.; Jayaraman, Chandrabose A. M.; Thangasamy, Selvaraj; Sathyanesan , Jeswanth (International Surgery Journal, 2023)
Ascariasis is an infection caused by Ascaris lumbricoides. Most of these infections are in the gastrointestinal tract. Its extraluminal infestations involving the liver, pancreas and biliary tract are rare and its complications are usually morbid. This aspect of extra intestinal manifestation is termed hepato biliary and pancreatic ascariasis. We report a 65 years old female with history of recurrent abdominal pain and on evaluation found to have Ascarial infection with complications involving liver, biliary and pancreas. She was optimized and taken up for surgery and she recovered well. The ascarial infections are generally seen in the paediatric populations and most of them are intestinal. Here we presented an adult with extraintestinal Ascariasis who had complications of hepatobiliary and pancreatic system which was managed successfully and she was presented for its rarity.